Tindak Kekerasan Pada Anak di Pondok Pesantren : Faktor Penyebab Serta Upaya Pencegahannya - Lailiyah, Kusroh; Saraya, Sitta; Suparno, Suparno (JURNAL LITBANG KOTA PEKALONGAN, 2025)
This research aims to determine the causes and efforts to prevent acts of violence in Islamic boarding schools. This research is library research. This research uses a qualitative approach through descriptive analysis methods based on literature studies obtained such as searching books, journal articles and other digital materials from the internet which are then used as analysis material. The results of this research show that there are many factors that cause acts of violence against students in Islamic boarding schools to still occur. These factors include the issue of unequal power relations between perpetrators and victims, the strong intensity of togetherness in Islamic boarding schools, Islamic boarding schools rarely select student input, especially Islamic boarding schools which still maintain the old way of educating students, during holidays and when students return home they do not receive adequate care. the same as Islamic boarding schools, the strict rules and regulations in Islamic boarding schools, problems with senior-junior relations, as well as closed attitudes and a tendency towards lack of cooperation in Islamic boarding schools. Therefore, in order to prevent acts of violence in Islamic boarding schools, there are several efforts that can be made, including building synergy between the roles of parents (guardians of students) and Islamic boarding school administrators, increasing legal awareness of students regarding acts of violence, forming a Team for Prevention and Handling of Violence (TPPK). ) in Islamic boarding schools and finally optimizing the role of supervision by the government. Keywords: Islamic boarding school, violence against children, violence in Islamic boarding schools